"Too‐Small‐To‐Survive" versus "Too‐Big‐To‐Fail" banks: The two sides of the same coin. Issue 3 (11th July 2018) - Grammatikos, Theoharry; Papanikolaou, Nikolaos I.
Abstract: In the recent crisis, the U.S. authorities bailed out numerous banks through TARP, whilst let many others to fail as going concern entities. Even though both interventions fully protect depositors, a bail out represents an implied subsidy to shareholders, which is not yet the case with closures where creditors are not subsidised. We investigate this non‐uniform policy, demonstrating that size and not performance is the decision variable that endogenously determines one threshold below which banks are treated as TSTS by regulators and another one above which are considered to be TBTF. We, hence, provide a pair of economic rather than regulatory cut‐offs for TBTF and TSTS banks. The shareholders and the other uninsured creditors of a distressed bank are not bailed out if the bank is considered to be TSTS. We further document that the less complex a bank is, the less likely is to be bailed out and, hence, to have all of its creditors protected.